Music for Macbeth - Locke, Matthew 1621-1677; Eccles, John 1668-1735; Leveridge, Richard 1670-1758 (A-R Ed., 2004)
Enthält: Tunes for "Macbeth" attributed to Matthew Locke ; Music for "Macbeth" by John Eccles ; Music for "Macbeth" by Richard Leveridge.
Keywords: Shakespeare, William - Macbeth - Vertonung; Shakespeare, William -- 1564-1616 -- Macbeth; Schauspielmusik; Anthologie